Determining vancomycin Etest MICs in patients with MRSA bloodstream infection does not support switching antimicrobials. Issue 3 (March 2017) - Hos, Nina J.; Jazmati, Nathalie; Stefanik, Danuta; Hellmich, Martin; AlSael, Halil; Kern, Winfried V.; Rieg, Siegbert; Wisplinghoff, Hilmar; Seifert, Harald; Kaasch, Achim J.
Summary: Objectives: Elevated vancomycin minimum inhibitory concentrations (MIC) have been reported to adversely affect clinical outcome in methicillin-resistant Staphylococcus aureus (MRSA) bloodstream infection (BSI). We therefore examined the association between vancomycin MIC and outcome considering various potential confounders. Methods: Clinical data and bacterial isolates were prospectively collected from patients with MRSA BSI from 2006 to 2012 as part of the Invasive Staphylococcus aureus Infection Cohort (INSTINCT) study. Antimicrobial susceptibility was assessed by Etest, broth microdilution (BMD) and VITEK 2. Bacterial genotypes were determined by spa typing. Using univariate and Cox regression analyses, we investigated the impact of low (≤1.0 mg/L) and high (≥1.5 mg/L) vancomycin Etest MIC on clinical outcomes. Results: Ninety-one MRSA BSI episodes were included, of which 79 (86.8%) were caused by spa types t003, t032 and t045. High vancomycin MICs were seen only if using Etest but not confirmed using standard reference BMD. When episodes were stratified into low and high vancomycin Etest MIC groups, 30-day overall mortality was 34.5% and 27.3%, respectively ( P = 0.64, OR 0.71; 95% confidence interval [CI] 0.27–1.79). Variables significantly associated with all-cause mortality in the Cox model were age ( P = 0.003), acute physiology score ( P = 0.0006), and Charlson comorbidity index ( P = 0.018). Conclusions: Vancomycin MICs may vary dependent on testing methodologies and local MRSA epidemiology. The patients' underlying disease and individual comorbidities rather than elevated vancomycin MICs determine adverse clinical outcomes in MRSA BSI. Routine Etest MIC testing of MRSA isolates is of limited value for treatment decisions. Highlights: Elevated vancomycin Etest MICs in MRSA BSI are not associated with adverse outcomes. The patient's comorbidities rather than vancomycin MIC determine clinical outcome. Vancomycin MICs vary with the susceptibility testing method used. Routine Etest MIC testing of MRSA isolates is of limited value for treatment decisions.